In Silico Evaluation of Phytochemicals from Amorphophallus muelleri as Potential PPARG Modulators in Polycystic Ovary Syndrome (PCOS): A Molecular Docking Study - Melati Ganeza; Enricko Hotma Jonifar Siregar (The International Journal of Medical Science and Health Research, 2025)
Objective: Polycystic Ovary Syndrome (PCOS) is a multifactorial endocrine disorder that affects women of reproductive age and is frequently associated with insulin resistance, hyperandrogenism, and metabolic abnormalities. Peroxisome Proliferator-Activated Receptor Gamma (PPARG) is a nuclear receptor involved in glucose and lipid metabolism and plays a pivotal role in the pathogenesis of PCOS. Amorphophallus muelleri is known to contain various fatty acid derivatives that may influence metabolic pathways through PPARG modulation. Methods: This study aimed to evaluate the binding affinity and interaction profiles of nine phytochemicals derived from A. muelleri toward PPARG using molecular docking analysis. The three-dimensional structure of PPARG (PDB ID: 3DZY) was retrieved from the Protein Data Bank, and docking simulations were conducted using the Molecular Operating Environment (MOE) software. Ligand preparation was performed through energy minimization using the MMFF94x force field, and the docking site was defined based on the co-crystallized ligand binding domain. Results: Docking results showed that all tested compounds had negative binding free energy values, indicating spontaneous interactions. Linoleic acid ethyl ester showed the strongest binding affinity with a docking score of –10.85 kcal/mol, followed by (9E)-9-octadecenoic acid (–10.42 kcal/mol) and 9-octadecenoic acid methyl ester (–10.20 kcal/mol). These compounds interacted with key residues in the PPARG ligand-binding domain, including Cys285, Tyr473, and His323, through hydrophobic interactions and hydrogen bonding, indicating a stable ligand–receptor complex. Conclusion: The findings of this study demonstrate that specific phytochemicals from Amorphophallus muelleri possess strong binding affinity and favorable interaction profiles with PPARG, supporting their potential relevance in the molecular mechanism underlying PCOS therapy.